Hate Speech and Ethno-Religious Violence in Nigeria - ugo okolie (Green Publisher Indonesia, 2022)
Hate speech is the precursor to ethno-religious violence in Nigeria. In recent times, no issue has generated widespread public comment in Nigeria more than the issues of hate speech and ethno-religious violence rocking the country and its sad consequences on national integration. Though, on the issue of hate speech, the provisions of Nigeria constitution and Nigeria Electoral Act are clear but the question is where to draw the line between political statements and hate speech. Therefore, this study explored the effect of hate speech on ethno-religious violence in Nigeria. A descriptive method was adopted and data was collected via a survey of 600 respondents comprises of Traditional Leaders, Christian leaders, Muslim leaders, Leaders of civil society groups and Youth leaders in South-South, South-West, South-East, North-West, North-central and North-East geopolitical zones of Nigeria. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 21. The study found that there is significant relationship between hate speech and ethno-religious violence in Nigeria. The study submits that, hate speeches in Nigeria are mostly credited to political leaders and their ethnic, religious or regional supporters. Requisite recommendations and conclusion were provided in the light of empirical and theoretical findings.